Agricultural land, coal mining, and urbanisation: A GIS-based analysis of land cover changes in Kosovo - Ibrahimi, Besarta; Bytyqi, Valbon; Agaj, Tropikë; Ramadani, Ibrahim (Brawijaya University, 2026)
The central sector of the Kosovo Plain, an area undergoing intense industrial and urban expansion, was selected to analyse the interrelationship between agricultural land use, coal mining operations, and land cover transformations. A geospatial analytical framework, using A GIS-based analytical framework was employed to assess land cover dynamics over the past two decades. This study critically examined the spatial and temporal patterns of land use change within one of the most densely populated and economically significant regions in both Kosovo and the broader Balkan area with the aim of quantifying the rate, magnitude, and direction of these changes to address the current gap in regional-scale assessments. Extensive lignite extraction central to Kosovo’s energy sector has driven the conversion of arable land into mining zones. However, the prevalence of open-pit lignite extraction has led to substantial environmental changes, particularly the conversion of arable land into mining zones. The study evaluated land cover transformations associated with environmental impacts between 2000 and 2018. Results indicated a 10% decline in agricultural land and a 59% increase in artificial surfaces between 2000 and 2018, reflecting intense urban and industrial expansion across the Kosovo Plain. These trends highlight accelerating anthropogenic pressures and underline the urgent need for integrated spatial planning and sustainable land management policies in Kosovo’s rapidly transforming lowlands.